Analysis of performance, emissions, and lubrication in a spark-ignition engine fueled with hydrogen gas mixtures (2022)
Hydrogen is one of the main alternative fuels with the greatest potential to replace fossil fuels due to its renewable and environmentally friendly nature. Due to this, the present investigation aims to evaluate the combustion characteristics, performance parameters, emissions, and variations in the characteristics of the lubricating oil. The investigation was conducted in a spark-ignition engine fueled by gasoline and hydrogen gas. Four engine load conditions (25%, 50%, 75%, and 100%) and three hydrogen gas mass concentration conditions (3%, 6%, and 9%) were defined for the study. The investigation results allowed to demonstrate that the injection of hydrogen gas in the gasoline engine causes an increase of 3.2% and 4.0% in the maximum values of combustion pressure and heat release rates. Additionally, hydrogen causes a 2.9% increase in engine BTE. Hydrogen’s more efficient combustion process allowed for reducing CO, HC, and smoke opacity emissions. However, hydrogen gas causes an additional increase of 14.5% and 30.4% in reducing the kinematic viscosity and the total base number of the lubricating oil. In addition, there was evidence of an increase in the concentration of wear debris, such as Fe and Cu, which implies higher rates of wear in the engine’s internal components.